Hygienic Status and Microbial Profile of Locally Produced Fermented Milk in Wukari North-East, Nigeria - Mohammed, Ikrimah Usman; Brown, Samuel Tamunoiyowuna Cockeye; Onyemaechi, Emmanuel (African Journal of Sciences and Traditional Medicine, 2025)
Background: Milk and its derivatives are widely consumed for their nutritional benefits; however, their improper handling and processing can lead to contamination with pathogenic microorganisms, posing significant public health risks. Aim: This study aimed to investigate the microbial quality of locally fermented milk products, sold in Wukari, North-East, Nigeria. Methods: A total of fifteen (15) fermented milk samples were collected from five different retail locations and analyzed for microbial contamination using standard microbiological techniques. Results: The results revealed high levels of bacterial contamination across all sampling sites, with total viable counts ranging from 0.3 × 10⁶ to 2.4 × 10⁶ CFU/mL. Coliform bacteria, including Escherichia coli and Klebsiella pneumoniae, were detected, indicating fecal contamination and poor sanitary conditions during processing and distribution. Staphylococcus aureus, a major foodborne pathogen, was identified in 27.1% of the total bacterial isolates, highlighting a potential risk of food poisoning. Other bacterial isolates included Pseudomonas aeruginosa, Bacillus subtilis, Enterobacter spp., and Staphylococcus epidermidis. Conclusion: The findings suggest that the unhygienic handling of fermented milk contributes to its microbial contamination, making it unfit for human consumption. This study emphasizes the need for improved hygiene practices, proper pasteurization, and strict regulatory measures to ensure the safety of locally produced dairy products. Public awareness campaigns should be conducted to educate dairy vendors and consumers about the health risks associated with contaminated milk.